Winter Floods in Reykjavík: Coaction of Meteorological and Soil Conditions - Anna Rut Arnardóttir 1993- (2020)
With Earth’s changing climate, the winters in cold climate regions are expected to be affected by rising temperatures and more frequent weather extremes. In maritime climate, such as in Reykjavík, winters are mild but characterized by frequent snow and freeze-thaw cycles. In this thesis the winter climate in Reykjavík is analyzed using meteorological data spanning almost 60 years, with the objective of gaining a better understanding of the snow characteristics and snowmelt in an urban environment. Changes in extreme winter weather were detected for variables related to frost, as winter days with freezing temperatures are becoming less frequent and less severe. Neither extreme snow depth nor extreme snowmelt are common in Reykjavík. Therefore, the risk of flooding due to snowmelt alone is not significant. The majority of extreme snowmelt events occur in the months from November through February when the effects of solar radiation are negligible. The main cause of urban winter flooding is found to be extreme rain on snow, especially when the ground is frozen. This emphasizes the need for reliable data on surface and soil conditions, which is currently not routinely monitored. We tested a simple model for predicting soil temperature. The model uses air temperature and snow depth as input variables, whereas soil moisture is taken to be constant. The model does not capture the soil temperature adequately during winter, especially when the soil freezes. Data comparison indicates that soil moisture greatly impacts the soil temperature and thus measurements of soil moisture would be of great value. The project is funded by The Rannís Research Grant